Factors associated with body weight status and internet addiction among malaysian university students in Penang: mixed method study before and during covid-19 pandemic - Isaac, Nesamalar (2024)
The Internet began as a divine gift to humans to enlighten society by transferring knowledge and making available all the information required for human well-being, growth, and prosperity. But as the internet grew popular, it created a set of problems on its own, one of the major ones being Internet Addiction (IA). In Malaysia, internet addiction is surfacing as a key problem among the younger generation. This mixed method study was performed to examine the factors associated with body weight status and internet addiction of Malaysian university students in Penang before and during COVID-19 pandemic. Data were collected from 352 Malaysian undergraduate students studying in public/ private colleges or universities. The level of internet addiction was determined based on Young’s internet addiction self-reported scale, and students were classified as no IA users (0.3%), mild IA users (56.8%), moderate IA users (37.5%), and severe IA users (5.4%). The multiple logistic analysis showed that the students gender (reference, female; male: OR = 7.795, P < 0.001), year of study (reference, third year of study; second year: OR = 5.924, P < 0.001), mother’s highest level of education (reference, primary level of education; secondary level of education OR = 0.095, P < 0.001; College/ University level of education OR = 0.021, P < 0.001), family size (reference, big family size; medium family size OR = 5.515, P < 0.001) made a unique statistically significant contribution to the model. The chi-square test was used to analyse the relationship between the students’ levels of internet addiction and lifestyle patterns and dietary behaviour. Irregular bedtimes were higher among severe internet addiction students than in mild internet addiction students. In Phase I study, all the students showed sedentary behaviour but in Phase II study physical activity was found to be higher among students with severe Internet Addiction. Diet quality among severe internet addiction students was also poorer than in moderate internet addiction students and mild internet addiction students. Moreover, improper dietary behaviour due to the loss of appetite, high frequency of snacking and skipping meals might cause imbalanced nutritional intake among severe internet users. In this study, it has been demonstrated that severely internet addiction students have inappropriate dietary behaviour and poor diet quality. Multinomial logistic regression analysis showed that the variable family size (reference, big family size; small family size OR = 0.060, P < 0.05) were found to be significant to predict the underweight. The internet addiction level (reference, no internet addiction; mild internet addiction OR = 412973.188, P < 0.05; moderate internet addiction OR = 143209.451, P < 0.001) and sleep quality (OR = 0.206, P < 0.001) were found to be significant to predict the normal weight of the students. Thirty-six students were subjected to a focus group discussion where they were motivated to share their experience in internet-related activities, the effect of internet usage on their significant aspects of life and the experience of withdrawal symptoms while trying to limit their online activity. They were also encouraged to share their perception of face-to-face personal interaction with family and friends, sports and other offline activities as compared to similar online activities. The findings of this study prove that there is a significant contribution of demographic and socio-economic factors to internet addiction among Malaysian university/college students in Penang. In addition, there is a significant contribution of demographic factors, internet addiction, and sleep quality to the body mass index of Malaysian university/college students in Penang.